Iddirs as Community-based Social Capital in the Amhara Region of Ethiopia: Case Study in Gende Woin Town of East Gojjam - Bazezew, Arega; Chanie, Wubliker (Ethiopian Journal of Social Sciences, 2015)
Though iddirs are vital in reducing social and/or idiosyncratic crises, there are formidable challenges in the implementation of this social capital for sustainable development. Experiences across Ethiopia in general and the study area in particular showed that less attention is given by the government. In addition, corruptions and embezzlement by iddir leaders hamper the potentials of iddirs in enhancing community-based development. The general objective of the study was to assess the role of ddirs in Gende Woin town as a case study site. In this study, mixed research approach was used, and questionnaire survey, key informant interview and focus group discussion were employed to collect primary data. A total of 118 households were covered by the questionnaire survey and six key informants and one focus group discussions were employed to collect qualitative data. Descriptive statistics and binary logistic regression modeling were used to analyze quantitative data. This study revealed that the majority (80%) of respondents were members of iddirs, among them 74% were maleheaded households. The majority of households perceived that iddir helps to organize and defend themselves at times of economic and social crises. However, the potentials of iddir in reducing shocks and mobilizing the community for development are underutilized due to lack of attention given by the previous and the current governments. Besides, financial constraints, lack of commitment among members and corruption perpetrated by their leaders and officials weakened the contributions of iddir for sustainable development. The binary logistic result showed that gender, income, family size and marital status were determinant factors for households’ to be membership in iddirs. In order to build up the capacity of iddirs, and maximize their involvement and efficiency in developmental activities both governmental and non-governmental organizations are expected to encourage and work together with iddirs.